A long-term high-fat, high-sucrose diet in Bama minipigs promotes lipid deposition and amyotrophy by up-regulating the myostatin pathway. (15th April 2016) - Ruan, Jinxue; Zhang, Yuanyuan; Yuan, Jing; Xin, Leilei; Xia, Jihan; Liu, Nan; Mu, Yulian; Chen, Yaoxing; Yang, Shulin; Li, Kui
Abstract: Skeletal muscle is as an important regulator of blood glucose and glycolipid metabolism and is closely related to motor ability. The underlying mechanisms by which dietary ectopic lipids in skeletal muscle prevents muscle growth remain elusive. We utilized miniature Bama swine as a model to mimic human obesity using prolonged dietary induction. After 23 months on a high-fat, high-sucrose diet, metabolic disorders were induced in the animals, which exhibited increased body weight, extensive lipid deposition in the skeletal muscle and amyotrophy. Microarray profiles demonstrated the up-regulation of genes related to fat deposition and muscle growth inhibition. We outline a clear potential pathway that in combination with increased 11β-hydroxysteroid dehydrogenase type 1, promotes expression of a major inhibitor, myostatin, by converting corticosterone to cortisol, which leads to the growth inhibition of skeletal muscle. This research provides new insights into the treatment of muscle diseases induced by obesity. Graphical abstract: Highlights: Long-term high-fat high-sucrose diet promotes lipid deposition. Long-term high-fat high-sucrose diet promotes amyotrophy. The amyotrophy is induced by upregulating the MSTN pathway.